Changes in the Thymus Gland of Rats Due to Food Intake - Ikhtiyor, Kiyamov (American Journal of Bioscience and Clinical Integrity, 2025)
Thymocyte proliferation, differentiation and apoptosis are the main processes of thymus morphogenesis and regeneration. At the stage of antigen-independent differentiation of T cells in the thymus, their mass death occurs by apoptosis. In this regard, the study of the influence of environmental factors on the main morphogenetic processes - cell proliferation and apoptosis in the thymus - is one of the foundations of immunotoxicological research. In recent decades, endocrinologists and immunologists have actively studied the effects of low-dose endocrine disruptors on the body. The most widespread disruptor on the planet is dichlorodiphenyltrichloroethane (DDT), which is found in all ecosystems of the continents and oceans, including the Arctic and Antarctic, and can persist in soil and water for a long time [1-3].